School Based Relaxation: Attempting Primary Prevention - Hiebert, Bryan; Kirby, Boelle; Jaknavorian, Armine (Canadian Journal of Counselling and Psychotherapy, 2011)
Three controlled studies involving progressive relaxation (PR) with public school were conducted. The first compared PR and biofeedback training with anxious grade ten students involved in public speaking. The second compared PR and an attention control group (Career Education) with grade eight students. The third study compared PR and an alternative Health and Personal Fitness elective with grade 11 and 12 students. The results indicate regular practice with PR produces reductions in both physiological, and paper and pencil dependent measures, but expectancy effects also can result in similar reductions in both types of measures. Higher program compliance coupled with greater reductions in anxiety and stress symptoms were observed in the grade 11 and 12 sample.